Data management and analytics for medicine and healthcare : second International Workshop, DMAH 2016, held at VLDB 2016, New Delhi, India, September 9, 2016, Revised selected papers /: second International Workshop, DMAH 2016, held at VLDB 2016, New Delhi, India, September 9, 2016, Revised selected papers. (2017) - Unknown
No abstract available